Zooplankton community structure in coastal waters off the strait of Malacca with emphasis on jellyfish - Abd. Razak, Siti Balqis (2016)
Jellyfish population is now reported to be increasing in many areas due to the environmental changes such as eutrophication and overfishing. However, jellyfish has been largely understudied and the absence of quantitative long-term data for the studied area impedes drawing conclusions on potential increasing densities. This study gives a comprehensive overview of the spatio-temporal distribution patterns of jellyfish in relation to pollution levels with turbidity and nutrient levels as the main markers in three areas namely Matang mangrove area (MM), Kuala Selangor coastal waters (KS) and Port Dickson coastal waters (PD). In each area, zooplankton and jellyfish samples were collected by the horizontal tow of a plankton net (140 μm mesh size) and bongo net (500 μm mesh size) at four different stations, bi-monthly between June 2010 and April 2011. Physico-chemical parameters were measured in situ using multi-parameter sonde (Model Hydrolab Surveyor 4). Water transparency was determined by Secchi disk and the turbidity was measured using turbidimeter at 2-m depth intervals. Water samples for the determination of total suspended solid (TSS), chlorophyll a and nutrients analyses were collected using a Niskin water sampler. Zooplankton and jellyfish abundance and biomass, chlorophyll a and nutrients were determined according to the standard methods. Salinity and dissolved oxygen concentrations in MM were significantly lower compared to the other two sites. Total suspended solid in KS was significantly higher compared to MM and PD. However, Turbidity, chlorophyll a, total nitrogen and total phosphorus in MM and KS were significantly higher compared to PD. A total of 12 zooplankton groups were recorded from the study areas throughout the sampling period. MM, KS and PD were dominated by copepods which comprised 79%, 74% and 79% of the total zooplankton. Among the sampling areas, KS (8243.1 ± 1344.9 ind. m-3) had the highest total mean density of zooplankton followed by MM (5486.3 ± 977.5 ind m-3) and PD (1389.0 ± 244.4 ind. m- 3). The zooplankton density in Port Dickson coastal waters was significantly lower compared to Matang mangrove area and Kuala Selangor coastal waters. Zooplankton biomass in KS, MM and PD were 13.2 ± 4.5 mg m-3, 11.3 ± 1.9 mg m-3 and 7.5 ± 1.9 mg m-3 respectively. There was no significant difference in the zooplankton biomass between the three areas. The jellyfish community comprised three major groups (Hydromedusa, Siphonophora and Ctenephora). Nineteen hydromedusae, two siphonophores and two ctenophores were recorded and a total of 23 species from 16 genera of jellyfish were identified from three different areas. Jellyfish density was significantly higher in Matang mangrove area (14.95 ± 3.60 ind. m-3) than those in Kuala Selangor coastal waters (1.53 ± 0.90 ind. m-3) and Port Dickson coastal waters (0.84 ± 0.25 ind. m-3). Similarly, the jellyfish biomass was highest in Matang mangrove area (162.12 ± 58.66 mgWW m-3) followed by Kuala Selangor coastal waters (22.65 ± 5.90 mgWW m-3) and Port Dickson coastal waters (15.32 ± 2.97 mgWW m-3). Generally, ctenophores were the most important group in MM, which dominated by Pleurobrachia sp. Meanwhile, hydromedusae (Eirene brevigona) and siphonophores (Lensia subtiloides) were dominated in KS and PD respectively. There was no significant difference in the species diversity (p>0.05) between the study areas. Jellyfish diversity in MM, KS and PD were H’ = 0.71 ± 0.18, H’ = 0.85 ± 0.25 and H’=1.08 ± 0.21 respectively. Soluble reactive phosphorus, chlorophyll a, total suspended solids, temperature and transparency are the main variables explaining the spatial and temporal distribution of jellyfish. This study also showed that besides the environmental parameters, location also influences the distribution of jellyfish. The jellyfish showed preference in the area which have more shelter (Matang mangrove area) compared to open waters (Kuala Selangor and Port Dickson coastal waters). This study provides baseline information to measure the potential increase of jellyfish abundance in MM, KS and PD.